The Effects of Credit Risk, Liquidity Risk, And Capital on Profitability in State-Owned Bank Association with Credit Restructuring as The Moderator - Aghata Christy Cahya Widhi Andini; Indraswari, Citra Rahayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Credit restructuring is an important things for managing credit risk and improving bank financial stability. However, the effect on profitability varies depending on the context and how this process affects credit risk, liquidity risk, and capital adequacy. This research aims to determine how the new policy of Indonesian Financial Accounting Standard 71 (PSAK 71) which regulates Allowance for Impairment Losses (CKPN) helps in supporting optimal credit restructuring, so that the variables analyzed include NPL, LDR, and CAR which affect ROA with credit restructuring as a moderation. The data analysis technique used is Moderated Regression Analysis (MRA). The data used is secondary data from Himbara's financial reports covering data from 2016 to 2023 on a quarterly basis. The research results found that partially NPL and CAR had an effect on ROA while LDR had no effect on ROA. While credit restructuring weakens the influence of NPL and CAR on ROA, credit restructuring strengthens the influence of LDR on ROA. In this research, credit restructuring acts as a pure moderator. Abstrak Restrukturisasi kredit adalah alat penting untuk mengelola risiko kredit dan meningkatkan stabilitas keuangan bank. Namun, efeknya terhadap profitabilitas bervariasi tergantung pada konteks dan bagaimana proses ini mempengaruhi resiko kredit, resiko likuiditas, dan kecukupan modal. Penelitian ini bertujuan untuk mengetahui bagaimana kebijakan baru Standar Akuntansi Keuangan Indonesia 71 (PSAK 71) yang mengatur tentang Cadangan Kerugian Penurunan Nilai (CKPN) membantu dalam mendukung restrukturisasi kredit yang optimal, sehingga variabel yang dianalisis meliputi NPL, LDR, dan CAR yang mempengaruhi ROA dengan restrukturisasi kredit sebagai moderasi. Teknik analisis data yang digunakan adalah Moderated Regression Analysis (MRA). Data yang digunakan adalah data sekunder laporan keuangan Himbara mencakup data dari tahun 2016 hingga 2023 secara triwulan. Hasil penelitian menemukan bahwa secara parsial NPL dan CAR berpengaruh terhadap ROA sedangkan LDR tidak berpengaruh terhadap ROA. Serta restrukturisasi kredit memperlemah pengaruh NPL dan CAR terhadap ROA, namun restrukturisasi kredit memperkuat pengaruh LDR terhadap ROA. Dalam penelitian ini restrukturisasi kredit berperan sebagai moderator murni.